País de gordos/país de muertos: Obesity, death and nation in biomedical and forensic genetics in Mexico. (December 2015) - García-Deister, Vivette; López-Beltrán, Carlos
This article provides a comparison between genomic medicine and forensic genetics in Mexico, in light of recent depictions of the nation as a ' país de gordos ' (country of the fat) and a ' país de muertos ' (country of the dead). We examine the continuities and ruptures in the public image of genetics in these two areas of attention, health and security, focusing especially on how the relevant publics of genetic science are assembled in each case. Publics of biomedical and forensic genetics are assembled through processes of recruitment and interpellation, in ways that modulate current theorizations of co-production. The comparison also provides a vista onto discussions regarding the involvement of genetics in regimes of governance and citizenship and about the relationship between the state and biopower in a context of perceived health crisis and war-like violence.